Development and Evaluation of Thermosensitive Hydrogels with Binary Mixture of Scutellariae baicalensis radix Extract and Chitosan for Periodontal Diseases Treatment - Chanaj-Kaczmarek, Justyna; Osmałek, Tomasz; Szymańska, Emilia; Winnicka, Katarzyna; Karpiński, Tomasz M.; Dyba, Magdalena; Bekalarska-Dębek, Marta; Cielecka-Piontek, Judyta (International journal of molecular sciences, 2021)
Scutellaria baicalensis root displays anti-inflammatory and antibacterial properties due to the presence of flavonoids, particularly baicalin, baicalein, and wogonin. Our work aimed at developing thermosensitive hydrogels containing a binary mixture of S. baicalensis radix lyophilized extract and chitosan as a novel approach for periodontal diseases treatment. Two types of chitosan were employed in preliminary studies on binary mixtures with S. baicalensis radix lyophilized extract standardized for baicalin, baicalein, and wogonin. Thermosensitive hydrogels were prepared of poloxamer 407, alginate sodium, and cellulose derivatives and evaluated in terms of rheological and mucoadhesive behavior. The presence of chitosan altered the release profile of active compounds but did not affect their in vitro permeation behavior in PAMPA assay. The synergistic effects of S. baicalensis radix lyophilized extract and chitosan toward ferrous ion-chelating activity, inhibition of hyaluronidase, and pathogen growth were observed. The thermosensitive gelling system showed shear-thinning properties, gelation temperature between 25 and 27 °C, and favorable mucoadhesiveness in contact with porcine buccal mucosa, which was enhanced in the presence of binary mixture of S. baicalensis radix extract and chitosan. The release tests showed that baicalin and baicalein were liberated in a prolonged manner with a fast onset from hydrogel formulations.